Reception Celebrating Judy Andreen's Swearing In as County Supervisor - Watkins, Howard::::::::: (1985)
Bruce Bronzan, Congressman Richard Lehman and Assemblymember Jim Costa Bronzan, Lehman and Costa campaign signs on wall